Kontribusi Guru Pendidikan Agama Katolik Sebagai Fasilitator dan Motivator dalam Meningkatkan Minat Belajar Siswa di SMP Salib Suci Kloangrotat-Waigete (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Education is an effort that is done consciously and planned in creating a learning atmosphere and learning process to develop their potential. Education includes all life experiences that support students to have a desire to learn and to understand and apply all the materials that have been learned. In the world of education, the role of a teacher is needed who plays a major role, especially in schools, namely the PAK teacher. PAK teachers act as facilitators and motivators in increasing students' interest in learning. This study aims to determine the contribution of PAK teachers as facilitators and motivators in increasing students' interest in learning. This research was conducted at SMPK Salib Suci Kloangrotat-Pogon Village, Waigete District, Sikka Regency, and East Nusa Tenggara. The type of research used is qualitative with a descriptive approach. Data collection techniques in this study used three methods, namely observation, interviews and documentation. The results of the study stated that there was a contribution from PAK teachers as facilitators and motivators in increasing students' interest in learning. PAK teachers in carrying out their roles as facilitators and motivators always help students and provide encouragement to increase students' interest in learning.